PROVISION OF CINNAMON BARK ETHANOL EXTRACT (Cinnamomum burmanii Blume) LOWER BLOOD SUGAR LEVELS HYPERGLYCEMIC WISTAR RATS - A, Bawa Putra, A.; P, SutirtaYasa, I W.; I. B, Putra Manuaba,; M, Siaka, I; M., Bakta, I; M, Jawi, I; Wijaya, Karna; I M, Oka Adi Parwata, Parwata,; M, Sukadana, I (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2022)
Cinnamon plant (Cinnamomum burmanii Blume) is a tall plant that contains secondary metabolites and is widely consumed by the community for generations which is used as a medicinal ingredient. The part of the cinnamon plant that is widely used by the community is the bark. Cinnamon bark extraction was carried out by maceration method in 96% ethanol followed by evaporation until a thick extract was formed. Furthermore, characterization was carried out and applied to hyperglycemic wistar rats by observing the decrease in blood sugar levels. The results showed that the moisture content was 9.62% and the yield was 14.74% and the phytochemical test showed that the cinnamon bark extract was positive for polyphenols and flavonoids. Cinnamon bark extract was able to reduce blood sugar levels of hyperglycemic wistar rats to reach normal which was observed from the third day after being injected with alloxan until the seventeenth day.